Neuroligin 2 R215H Mutant Mice Manifest Anxiety, Increased Prepulse Inhibition, and Impaired Spatial Learning and Memory - Chen, Chia-Hsiang; Lee, Pin-Wei; Liao, Hsiao-Mei; Chang, Pi-Kai (Frontiers in Psychiatry, 2017)
Neuroligin 2 (NLGN2) is a post-synaptic adhesion protein that plays an essential role in synaptogenesis and function of inhibitory neuron. We previously identified a missense mutation R215H of the NLGN2 in a patient with schizophrenia. This missense mutation was shown to be pathogenic in several cell-based assays. The objective of this study was to better understand the behavioral consequences of this mutation in vivo. We generated a line of transgenic mice carrying this mutation using a recombinant-based method. The mice were subjected to a battery of behavioral tests including open field locomotor activity assay, pre-pulse inhibition assay, accelerated rotarod test, novel location and novel recognition tests, elevated plus maze test, and Morris water maze test. The transgenic animals were viable and fertile, but the Nlgn2 R215H knock-in (KI) homozygous mice showed growth retardation, anxiety-like behavior, increased prepulse inhibition, and impaired spatial learning and memory. There was no significant interaction between sex and genotype in most behavioral tests; however, we observed a significant interaction between sex and genotype in elevated plus maze test in this study. Also, we found that the Nlgn2 R215H homozygous KI mice did not express the neuroligin 2 protein, resembling Nlgn2 knockout mice. Our results demonstrate that Nlgn2 R215H KI homozygous mice manifest several behavioral abnormalities similar to those found in psychiatric patients carrying NLGN2 mutations, indicating that dysfunction of neuroligin 2 contributes to the pathogenesis of certain psychiatric symptoms commonly present in various mental disorders, not limited to schizophrenia.